Islamic calligraphy in contemporary art of Malaysia. Vol. 1 / Nor Azlin Hamidon - Hamidon, Nor Azlin (2012)
This research entitled Islamic Calligraphy in Contemporary Art of Malaysia contribute to the most neglected area in the development of the history of art of Malaysia. The combination of three different traditions - Islam, Malay and Western traditions had made significant marks on the form, content and context of the Islamic calligraphy in the Contemporary Art of Malaysia. The objectives of this study are firstly to document contemporary art works of Malaysia that constitutes of Islamic calligraphy. Secondly, is to establish the styles through formal analysis, in terms of its size, medium, techniques, orientation, shape and type of calligraphy. Thirdly, is to uncover the themes of the calligraphy, the sources of quotation and its meanings. Fourthly, is to discover the underlying factors and forces that influence the production of these art works; and finally, to discern the spiritual manifestation from the art works. This study, which covers contemporary art works of Malaysian artists since 1940's until 2005, managed to give a better picture on aspects that have been neglected by the art historians regarding Islamic and Western impact on the art of Malaysia. In doing so, the researcher is inclining to the theory of Iconology proposed by Erwin Panofsky that covers three levels of analysis, i.e. the pre-iconographical description, iconological analysis and iconographical interpretation. Since this research deals with the content and context of the Islamic art, the Panofsky's approach has been evaluated within the classification of knowledge by al-Imam al-Ghazzali. A new level of interpretation that deals with spiritual dimension was introduced in the theory of iconology. The findings highlighted that the educational background determines the major styles of Islamic Contemporary Art of Malaysia. The style was expressive, if the artists were trained in western-educational system, whereas the traditional calligraphers tend to produce hard-edged calligraphy adhering to the rules of writing calligraphy. Within these styles, there was a fusion of these two traditions that made Malaysia as a melting pot. Artists of different races practice Islamic calligraphy in their art works as a manifestation of cultural integration and realization of political policies. The external forces, such as Islamic resurgence had been one of the main factors that increase the production of art works. On the other hand, internal forces and personal motivation based on spiritual drives and inner consciousness had become a major factor that drives the artists to commit themselves with this art throughout their lives. Finally, the findings of this research formulated five main categorizations of Islamic contemporary calligraphy, based on two main considerations: meaning and style. They are Traditional Calligraphy, Rudimentary/Modern Calligraphy, Abstract Calligraphy, Marginal Calligraphy and Gestural/Pseudo Calligraphy. These findings are so meaningful, as they enlighten future area of studies pertaining to the History of Islamic Art in Malaysia as well as the South East Asia regions.